Identifying the need for surgical intervention in pediatric bacterial meningitis: single-center experience - Boyraz, Merve; Yüce, Servet; Özel, Abdulrahman; Örmeci, Mehmet Tolgahan; Akkaya, Süleyman; Köksal Atiş, Şeyma; Botan, Edin (Frontiers in Pediatrics, 2025)
BackgroundIntracranial complications of bacterial meningitis can arise at any stage and may necessitate neurosurgical intervention. This study evaluates clinical, laboratory, and imaging findings predictive of surgical need in these cases.MethodsBetween 2013 and 2023, 52 pediatric patients with severe neurological symptoms due to bacterial meningitis were admitted to PICU at Van Training and Research Hospital. Patients were classified into two groups: those with intracranial complications (Group 1, n = 36) and those without (Group 2, n = 16). Group 1 was further divided into those requiring surgery (Group 1B, n = 9) and those not (Group 1A, n = 27). Statistical analyses were conducted.ResultsAmong 52 patients (67.3% male, mean age 76.7 ± 72.0 months), 36 (69.2%) developed intracranial complications, and 9 (17.3%) required surgery. CRP levels were significantly higher in Group 1B (226 mg/dl) than in Group 1A (63 mg/dl) (p < 0.001). Significant differences were also found in CSF protein/glucose ratio (p = 0.011) and CSF glucose levels (p = 0.049). Subdural empyema (SDE) developed in 25 cases, with single-area involvement significantly more frequent in surgical cases (77.8% vs. 12.5%, p = 0.012). ROC analysis was performed for CSF protein/glucose, CSF glucose, and serum CRP values.ConclusionCRP >150 mg/dl, CSF glucose <6.75 mg/dl, and protein/glucose ratio >18.9 indicate high surgical risk. MRI is recommended for localization, with early neurosurgical consultation and multidisciplinary management for cases with single-area empyema.